Polarization‐Insensitive Metalens with Extended Focal Depth and Longitudinal High‐Tolerance Imaging. Issue 2 (11th November 2019) - Zang, XiaoFei; Xu, WeiWei; Gu, Min; Yao, BingShuang; Chen, Lin; Peng, Yan; Xie, JingYa; Balakin, Alexey V.; Shkurinov, Alexander P.; Zhu, YiMing; Zhuang, SongLin
Abstract: Lenses with an extended focal depth have crucial applications in high‐precision optical alignment systems and optical disk readout systems. However, further development of lenses with an extended focal depth under radial and angular modulation is limited because of fabrication difficulties. Metasurfaces, 2D metamaterials, have shown unprecedented capabilities in the manipulation of the intensity, phase, and polarization of electromagnetic waves. Here, based on geometric metasurfaces, an approach for realizing a terahertz metalens is proposed and experimentally demonstrated with simultaneous extended focal depth and polarization insensitivity. Under the illumination of arbitrarily polarized light, this metalens shows a focal depth of ≈23 λ along the propagation direction, resulting in an ultralong longitudinal working distance. As a proof‐of‐concept, longitudinal high‐tolerance imaging based on the metalens is demonstrated. The unique approach for designing polarization‐insensitive metalenses with an extended focal depth may find applications in imaging, lithography, and information processing. Abstract : A metalens can form a focal spot with a 23λ focal region under the illumination of arbitrarily polarized THz waves, leading to a polarization‐insensitive metalens with an extended focal depth. This metalens has application in longitudinal high‐tolerance imaging. This design not only provides a platform for manipulating the focal spot depth but also opens an avenue for longitudinal high‐tolerance imaging.